Metode Peer Education Berpengaruh Terhadap Tingkat Pengetahuan Remaja Tentang HIV/AIDS - I Made Widastra; I Made Oka Bagiarta (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
The research aims to prove that the administration of peer education methods influence the level of knowledge of adolescents about HIV/AIDS. The study was conducted using pre-experimental research design, namely a one-group pre-post test design. Samples 40 individuals obtained using a purposive sampling technique. The study was conducted at SMK Pariwisata Kertayasa Ubud for two weeks with the increased knowledge of knowledge is less (42.5%) and sufficient knowledge (57.5%) increased significantly to be good (100%). Based on the test of paired t test (p 0.05), obtained a significance value of p = 0.000 α 0.05. The results of this study indicate that there is a significant effect of method of peer education on adolescent knowledge levels about HIV/AIDS